Model predictive current control for maximum power point tracking of voltage source inverter based grid connected photovoltaic system - Satyanarayana Burada; Kottala Padma (Institute of Advanced Engineering and Science, 2023)
Due to the high demand of grid connected photovoltaic systems, there is a need to track the maximum power point of the PV system. As the output of PV system is dc, there should be a converter, acting as medium between PV system and dc bus capacitor to track maximum power at all the loads. Usually boost converter is acting as medium between PV system and dc link capacitor as the duty cycle of the insulated-gate bipolar transistor in boost converter is in between 0 to 1 for maximum loads during maximum power point tracking (MPPT). To make PV system stable, the balance point is dc bus. If the dc bus voltage is constant, the system will be stable. Then the transfer power will just depend on current. For this purpose, the active current reference signal is to be generated by setting up the reference voltage across dc bus. Here to generate active reference current, PI controller is used and the reference voltage is taken according to the peak voltage of the inverter output voltage. The proposed control strategy was evaluated on a three-phase inverter linked to the grid and supplied by the PV system, which is working under varying irradiation conditions.